The evaluation research: A comparative analysis of qualitative and quantitative research methods - Ghafar, Zanyar Nathir (Journal of Language, Literature, Social and Cultural Studies, 2024)
Researchers often use a mixture of qualitative and quantitative approaches drawn from various fields. It is possible to record or quantify quantitative data. Qualitative data are descriptive, linguistically related, and rely on interpretation. Quantitative data provides information such as how many, how much, or how often something occurs. On the other hand, qualitative data could assist us in comprehending the processes, causes, and occurrences of activities. Each approach has many advantages as well as some disadvantages. This research aims to evaluate the various language testing and assessment approaches and compare and contrast their benefits and drawbacks. These advantages included the opportunity to learn more about the development, administration, and interpretation of assessments and tests and the capability to research test-takers behavior, perceptions, attitudes, and understanding. The study's findings showed that the amount of time required gathering data using quantitative research techniques is much less than the amount of time required collecting data using qualitative research methods. Quantitative research methods, on the other hand, have several drawbacks, such as the difficulty of explicating what a researcher means when using a specific word and the fact that these methods can only provide an overarching comprehension of the topic being studied